2012
DOI: 10.1038/ng.2484
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study dissects the genetic architecture of oil biosynthesis in maize kernels

Abstract: Maize kernel oil is a valuable source of nutrition. Here we extensively examine the genetic architecture of maize oil biosynthesis in a genome-wide association study using 1.03 million SNPs characterized in 368 maize inbred lines, including 'high-oil' lines. We identified 74 loci significantly associated with kernel oil concentration and fatty acid composition (P < 1.8 × 10(-6)), which we subsequently examined using expression quantitative trait loci (QTL) mapping, linkage mapping and coexpression analysis. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
643
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 696 publications
(657 citation statements)
references
References 72 publications
9
643
0
5
Order By: Relevance
“…The data set in this study has been successfully used in exploring the genetic architecture of oil biosynthesis and accumulation in maize kernel, which is a typical quantitative trait controlled by polygenic loci 46 . The results showed that 74 highly significantly associated loci were responsible for oil concentration and fatty acid composition 5 . Twenty-one of the 74 associated polymorphisms were located in known fatty acid biosynthesis genes, including the three previously reported loci DGAT1-2, FATB and FAD2.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The data set in this study has been successfully used in exploring the genetic architecture of oil biosynthesis and accumulation in maize kernel, which is a typical quantitative trait controlled by polygenic loci 46 . The results showed that 74 highly significantly associated loci were responsible for oil concentration and fatty acid composition 5 . Twenty-one of the 74 associated polymorphisms were located in known fatty acid biosynthesis genes, including the three previously reported loci DGAT1-2, FATB and FAD2.…”
Section: Discussionmentioning
confidence: 89%
“…In the last decades, many genes that are essential for maize kernel development and nutrient accumulation have been characterized using genetic mutants or map-based cloning methods 2,3 . Linkage or association analyses have identified more than a hundred of loci or candidate genes underlying kernel-related traits 4,5 . Moreover, the transcriptome profiles of maize kernel have already been analysed in two elite inbred lines [6][7][8] , identifying candidate genes and coexpression networks involved in kernel developmental pathways.…”
mentioning
confidence: 99%
“…To model the biomass and evaluate the measuring accuracy of RAP-Maize, a subset of the maize association mapping panel (Yang et al, 2011;Li et al, 2013; 387 individuals from 100 genotypes with three to four replicates each [see "Materials and Methods"]) was grown separately and measured for three traits automatically and manually in four stages. In the previous study (Yang et al, 2014), the side-projected area (SA) showed good correlation with manually measured fresh weight and dry weight, with r 2 .…”
Section: Performance Evaluation Of Rap-maizementioning
confidence: 99%
“…Fertilizing was carried out at sowing, V5, and V9 stage (60 kg of water + 370.68 g of carbamide + 330.76 g of potassium dihydrogen phosphate + 94.24 g of potassium chloride, to be fully dissolved with 150 mL of liquid fertilizer for each plant per time). A subset of the association mapping population (Yang et al, 2011;Li et al, 2013), including 100 diversity inbred lines, was randomly selected and sown on the same day in a phenotypic platform with four replications, screened using the RAP, and measured manually at 36, 48, 60, and 70 d after sowing (Supplemental Table S11). Destructively measured traits were obtained for biomass modeling, and the correlation between manual measurement and automatic measurement was calculated.…”
Section: Plant Materials Growth Conditions and Experiments Designmentioning
confidence: 99%
See 1 more Smart Citation